An In Vitro Microneutralization Assay for SARS‐CoV‐2 Serology and Drug Screening. Issue 1 (25th June 2020) - Amanat, Fatima; White, Kris M.; Miorin, Lisa; Strohmeier, Shirin; McMahon, Meagan; Meade, Philip; Liu, Wen‐Chun; Albrecht, Randy A.; Simon, Viviana; Martinez‐Sobrido, Luis; Moran, Thomas; García‐Sastre, Adolfo; et al.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) emerged in the city of Wuhan, Hubei Province, China, in late 2019. Since then, the virus has spread globally and caused a pandemic. Assays that can measure the antiviral activity of antibodies or antiviral compounds are needed for SARS‐CoV‐2 vaccine and drug development. Here, we describe in detail a microneutralization assay, which can be used to assess in a quantitative manner if antibodies or drugs can block entry and/or replication of SARS‐CoV‐2 in vitro. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Microneutralization assay to test inhibition of virus by antibodies (purified antibodies or serum/plasma) Basic Protocol 2 : Screening of anti‐SARS‐CoV‐2 compounds in vitro Support Protocol : SARS‐CoV‐2 propagation